Segmentation of Mobile Internet Users in The Indonesian Context: Insight for Mobile Internet Product Development Management - Daryanti, Sri; Simanjuntak, Kristina Uli (The South East Asian Journal of Management, 2016)
This study strives to identify the market segment for mobile Internet based on demographic characteristics and technology usage behavior attributes. Market segment analysis is one of the most important factors for target market identification of products or services. Segmentation analysis is also very crucial to the success of product development management to ensure that products reach their potential customers or their target market effectively with the right marketing strategies, thereby ensuring peak profitability. In this segmentation research project, data were collected through a paper-based survey using nonprobability sampling among 232 respondents. Based on cluster analysis, the mobile Internet segment in Indonesia can be divided into four groups: savvy users (35.8%), loyal users (27.6%), value users (27.6%) and traditional users (9.9%). The study found that factors which clearly differentiate mobile Internet segments are: mobile data usage during web browsing, communication activity including social media activity, game activity, and price sensitivity.